Different local, innate and adaptive immune responses are induced by two commercial Mycoplasma hyopneumoniae bacterins and an adjuvant alone - Beuckelaere, Lisa; Haspeslagh, Maarten; Biebaut, Evelien; Boyen, Filip; Haesebrouck, Freddy; Krejci, Roman; Meyer, Evelyne; Gleerup, David; De Spiegelaere, Ward; Devriendt, Bert; Maes, Dominiek (Frontiers in Immunology, 2022)
Enzootic pneumonia still causes major economic losses to the intensive pig production. Vaccination against its primary pathogen, Mycoplasma hyopneumoniae, is carried out worldwide to control the disease and minimize clinical signs and performance losses. Nonetheless, the effects of both infection with, and vaccination against Mycoplasma hyopneumoniae on the innate and adaptive immune responses remain largely unknown. Therefore, we conducted a study in which piglets were injected once with a commercial bacterin V1 or V2, or the adjuvant of V1 (A) to investigate their effect on local, innate and adaptive immune responses. Three weeks after vaccination, piglets were challenge infected with M. hyopneumoniae and euthanized four weeks later to assess vaccine efficacy via macroscopic and microscopic evaluation of lung lesions. Blood and broncho-alveolar lavage fluid (BAL) samples were collected to measure antibody responses, cellular immunity, BAL cytokine levels and BAL M. hyopneumoniae DNA load as well as cytokine secretion by monocytes. After vaccination, proliferation of antigen-specific CD3+ T cells and a higher percentage of TNF-α+ CD8+, and TNF-α+ and TNF-α+IFN-γ+ CD4+CD8+ T cells was seen in V1, while proliferation or a significant increase in cytokine production by different T cell subsets could not be observed for animals from V2. Interestingly, LPS-stimulated blood monocytes from V1 and A secreted less IL-10 on D7. After challenge, higher levels of IgA, more IL-10 and less IL-1β was detected in BAL from V1, which was not observed in V2. Animals from A had significantly more IL-17A in BAL. The macroscopic lung lesion score and the M. hyopneumoniae DNA load at euthanasia was lower in V1, but the microscopic lung lesion score was lower in both vaccinated groups. In conclusion, these results indicate that the two commercial bacterins induced different local and adaptive immune responses, that the adjuvant alone can reduce anti-inflammatory innate immune responses, and that both vaccines had a different efficacy to reduce Mycoplasma-like lung lesions and M. hyopneumoniae DNA load in the lung.